Penerapan Metode Demonstrasi untuk Meningkatkan Pemahaman Siswa mengenai Sifat-Sifat Cahaya pada Mata Pelajaran IPA Kelas IV di SDN 10 Belida Darat Tahun Ajaran 2018/2019 - Hastuti, Sri (Yayasan Sembilan Pemuda Indonesia, 2021)
This classroom action research aims to increase students' understanding of concepts in science subjects, namely the material properties of light by applying the demonstration method. This study involved 18 students of Class IV SD Negeri 10 Belida Darat for the 2018/2019 academic year. The research was conducted in 2 cycles and each cycle consisted of 4 activities, namely planning, action, observation, and reflection. The results showed that the class average increased from 53.06 (pre-action) to 64.17 (cycle I) and 72.22 (cycle II). In addition to the increase in class average scores, student learning completeness also increased from 44.44% (pre-cycle) to 66.67% (end of cycle I) and 94.44 (end of cycle II).